Pengaruh Permainan Tradisional Engklek Terhadap Perkembangan Motorik Kasar Anak Usia 5-6 Tahun Di TK Bhineka Karya Tunggulsari Dan Tk Islam Bhakti VIII Wonorejo - PERWITASARI, ANISA CANDRA; , Isnaini Herawati, SST.FT., M.Sc (2016)
Background: The development of technology the longer growing advanced, many people are spoiled by modern technology such as televisions, mobile phones, playstation and smartphones. But the other side of the development of such technologies can cause harm, especially for children who are experiencing growth and development. The impression of the development of modern technology is not always has positive impact on the children world. The phenomenon happened lately, the ere a lot of digital games that negatively impacted the child (Herani, 2013). It will cause the child's activity will be minor because children are busy with the gadgets, resulting in gross motor development was delayed (Herani, 2013). One of the media game that could stimulate gross motor development of Early childhood is a traditional game of Engklek (Rahyubi, 2012). Objective: To determine the important role of the traditional game of Engklek on the gross motor development of children aged 5-6 years. Methods: The study of this research is Quasi Experiment research or appearance experimental. The Desain of this research is pre and post test two group design compared between the two groups: the treatment group were given game training of Engklek for 4 weeks, 3 times training a week with a duration for 10 minutes. Measuring equipment for gross motor skills using the Gross Motor Development Test (TGMD). Data were analyzed using the Wilcoxon signed rank test to test the effect and influence of different test using Man Whitney test. Results: There was the influence of the traditional game of Engklek on the gross motor development of children aged 5-6 years after the statistical test using Wilcoxon test showed a p-value of 0.001 in the treatment group and the control group getting the p-value of 0.004. While the influence of different test with man Whitney test showed a p-value of 0.000.